TRANSITIONAL JUSTICE: THE REINTEGRATION OF CHILD SOLDIERS THROUGH POST-CONFLICT METHODS OF JUSTICE - Barbosa-Fohrmann, Ana Paula (Novos Estudos Jurídicos, 2015)
This paper examines the problematic of child soldiers, based on inter alia the strategy of research and study of the United Nations Office of the Special Representative of the Secretary-General for Children and Armed Conflict and on the priorities of the Machel Study. Here, national and international law will be applied on countries where children are recruited by armed groups. Concerning domestic jurisdiction alternative or traditional methods of justice as well as formal legal methods will be addressed. Specifically, this paper will focus on three main subjects: 1) the possibility of prosecution and judgment of adolescents, who participated in armed conflicts; 2) prosecution and judgment of war lords and 3) civil reparation proportional to the damage caused by an armed conflict. These three subjects will be construed according to (traditional or alternative and formal) national and international law. Finally, some recommendations will be made in order to improve the system of reintegration of child soldiers in post-conflict countries.